TGFβ1-Smad canonical and -Erk noncanonical pathways participate in interleukin-17-induced epithelial–mesenchymal transition in Sjögren’s syndrome - Sisto, Margherita; Lorusso, Loredana; Ingravallo, Giuseppe; Ribatti, Domenico; Lisi, Sabrina (Laboratory investigation, 2020)
Interleukin-17 (IL-17) is a pleiotropic cytokine that plays a primary role in triggering epithelial–mesenchymal transition (EMT) in many chronic inflammatory diseases. EMT plays a critical role in the progression of salivary gland (SG) fibrosis in primary Sjögren’s syndrome (pSS). This study focused on the activation of the canonical TGF-β1/Smad2/3 and noncanonical TGF-β1/Erk1/2 pathways in IL-17-dependent TGFβ1-induced EMT in human SG epithelial cells (SGEC) derived from healthy subjects. The expression of phosphorylated Smad2/3 and Erk1/2 during IL-17 treatment-stimulated EMT was evaluated in healthy SGEC. Cotreatment with IL-17 and specific TGFβ receptor type I kinase inhibitor SB431542, or Erk 1/2 inhibitor U0126, abrogates the corresponding morphological changes and EMT phenotypic markers expression in healthy SGEC. Interestingly, inhibition of canonical TGFβ1/Smad2/3 signal transduction had no effect on activation of the noncanonical TGFβ1/Erk1/2/EMT pathway, suggesting that the two pathways act independently in activating IL-17-dependent EMT in SGEC. Epithelial–mesenchymal transition (EMT) plays a critical role in the progression of salivary gland (SG) fibrosis in primary Sjögren’s syndrome. This study demonstrates the IL-17-dependent activation of EMT in human SG epithelial cells that occurs through both the canonical TGF-β1/Smad2/3 and noncanonical TGF-β1/Erk1/2 pathways.